The Efficacy Study of Duramectin, Oxfendazole, Piperazine, and Pyrantel pamoate Against Gastrointestinal Worms In Horses In Yogyakarta Special Region*) - Yuriadi Yuriadi; Ida Tjahajati; Soedarmanto Indarjulianto; Irkham Widiyono (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
This research aimed at determining the efficacy of duramectin, oxfendazole, piperazine, and pyrantelpamoate against gastrointestinal worms in horses in Yogyakarta Special Region and Central Java. The object of research involved 40 horses diagnosed with gastrointestinal worm infection. Prior to the research, all of the horses were subjected to examination for clinical symptoms and parasitology laboratory checkup for signs of worm eggs in their feces, and they were pronounced positive for experiment animals with at least 150 eggs per gram of feces per horse. The research horses were weighed to determine the dose of worm medication to be used. The research horses are divided into four treatment groups, each group consists of ten horses. Group I was given duramectin with a dose of 0.2 mg/kg of body weight. Group II was given oxfendazole with a dose of 7.5 mg/kg of body weight, Group III was given 125 mg Piperazin treatment per kilogram of body weight and Group IV was given pyrantelpamoate with a dose of 20 mg/kg of body weight. After receiving themedication, the horses were observed to document the progress in terms of clinical symptoms and the amount and type of worm eggs in their feces every three days for four times in a row. The research data results were tabulated and were descriptive-comparatively analyzed.The research result showed varying efficacy level of worm medication for horses. Oxfendazole kills Strongylus and Parascaris worms. Duramectin kills Strongylus worms and reduce some of the Parascaris worms. Piperazineandpyrantelpamoate kills the Strongylus wormsand reduce some of the Parascaris.